2013
DOI: 10.1155/2013/478516
|View full text |Cite
|
Sign up to set email alerts
|

Nosology of Juvenile Muscular Atrophy of Distal Upper Extremity: From Monomelic Amyotrophy to Hirayama Disease—Indian Perspective

Abstract: Since its original description by Keizo Hirayama in 1959, “juvenile muscular atrophy of the unilateral upper extremity” has been described under many nomenclatures from the east. Hirayama disease (HD), also interchangeably referred to as monomelic amyotrophy, has been more frequently recognised in the west only in the last two decades. HD presents in adolescence and young adulthood with insidious onset unilateral or bilateral asymmetric atrophy of hand and forearm with sparing of brachioradialis giving the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 34 publications
6
40
0
1
Order By: Relevance
“…EMG of the affected muscles shows evidence of chronic denervation, with or without acute denervation changes (fasciculations, positive sharp waves, and fibrillations potentials). However, apparently healthy muscles may also show abnormal EMG findings [4]. …”
Section: Discussionmentioning
confidence: 99%
“…EMG of the affected muscles shows evidence of chronic denervation, with or without acute denervation changes (fasciculations, positive sharp waves, and fibrillations potentials). However, apparently healthy muscles may also show abnormal EMG findings [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, Misra et al and Ammendola et al found no significant differences between standard and flexed position for F-wave parameters, suggesting a different etiology for HD than flexion myelopathy (2,12). Hassan et al and Ghosh et al showed no electromyographic abnormalities of C5 and C6 myotomes (27,28).…”
Section: Discussionmentioning
confidence: 96%
“…Other typical clinical features include "cold paresis", worsening of symptoms with cold exposure, and no abnormalities of tendons reflexes, sensory disturbance and pyramidal signs (14,15,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations